The Advancing Roles of Exosomes in Breast Cancer - Wang, Xi; Sun, Chunxiao; Huang, Xiang; Li, Jun; Fu, Ziyi; Li, Wei; Yin, Yongmei (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer (BC) develops from breast tissue and is the most common aggressive malignant tumor in women worldwide. Although advanced treatment strategies have been applied and reduced current mortality rates, BC control remains unsatisfactory. It is essential to elucidate the underlying molecular mechanisms to assist clinical options. Exosomes are a type of extracellular vesicles and mediate cellular communications by delivering various biomolecules (oncogenes, oncomiRs, proteins, and even pharmacological compounds). These bioactive molecules can be transferred to change the transcriptome of target cells and influence tumor-related signaling pathways. Extensive studies have implicated exosomes in BC biology, including therapeutic resistance and the surrounding microenvironment. This review focuses on discussing the functions of exosomes in tumor treatment resistance, invasion and metastasis of BC. Moreover, we will also summarize multiple interactions between exosomes and the BC tumor microenvironment. Finally, we propose promising clinical applications of exosomes in BC.